UNDULATING CHANGES IN TRAINING LOADS IN PHYSICAL EDUCATION LESSONS - Ibadullaev Balhoja (PEDAGOGS, 2024)
Abstract: In fact, the gradual increase in loads can be rectilinear, gradual or undulating. For sports training, a more undulating dynamics is considered characteristic. The reason for this is, finally, the high level of requirements for the functional and adaptive capabilities of the athlete's body.